Bias Correction for Eta Squared in One-Way ANOVA - Xiaofeng Steven Liu (Methodology, 2022)
Eta squared is a popular effect size, but contains positive bias. Bootstrapping can be used to remove the bias from eta squared. Compared to epsilon squared and omega squared, bootstrap bias correction does not make distributional assumption, and it is easy to implement. A real example and computer simulations are included to illustrate its application. The bootstrap bias-corrected eta squared shows very little bias, and it serves as a good alternative to eta squared and epsilon squared, the latter of which can turn negative in some circumstances.